Zero velocity regions near forward and rare points of circular cylinder: A heat and mass transfer study - T. Salahuddin; Mair Khan; Yu-Ming Chu (Ain Shams Engineering Journal, 2021)
This paper examines the unsteady two-dimensional boundary layer heat and mass transfer features of viscoelastic fluid flow near the neighborhood of forward and rare stagnation points. The heated circular cylinder is immersed in a viscoelastic fluid and the forward and rare stagnation points occurs near downward and upward directions of the cylinder respectively. The velocity near the surface of the cylinder is assumed to be zero and at very large distance from cylinder a uniform free stream velocity is spontaneously started in vertical direction. A non-similar transformation reduces the set of partial differential equations into non-similar partial differential equations. The transformed non-linear partial differential system is solved by using Keller box method. This technique shows well-behaved solutions for the steady-state (large time) and transient (small time) flows near the boundary layer region. Moreover, the body force present in this phenomena is in the form of convection which gives assisting (greater than zero) and opposing flows (less than zero). Parameters like the viscoelastic parameter, the convection parameter and the stagnation point parameter (forward and rare stagnation points) are found to control the flow field. Moreover, the Schmidt and the Prandtl numbers are used to control the concentration and temperature distributions. Features of several parameters on the non-dimensional concentration, temperature, local Nusselt and Sherwood numbers are viewed through graphs (2-d and 3-d) and tables. Contour images are plotted in order to visualize the three dimensional surface into two dimensional plane.